1999
DOI: 10.1021/ja983524w
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Thermal Transformation, a New Way to Enantiopure Biphenyl-Bridged Titanocene and Zirconocene Complexes:  Efficient Catalysts for Asymmetric Imine Hydrogenation1

Abstract: Enantiopure biphenyl-bridged titanocene and zirconocene complexes were obtained, by an asymmetric thermal transformation of the binaphthol complexes formed from the metallocene racemates and subsequent transformation to the corresponding dichlorides, in practically quantitative yields. Increased rates of this transformation in the presence of O2 gas or TEMPO indicate a radical reaction mechanism. The biphenyl-bridged titanocene enantiomers give rise to an efficient asymmetric catalysis for the hydrogenation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 11 publications
1
35
0
Order By: Relevance
“…In recent years a variety of chiral metal catalysts have been successfully applied to this reaction. The chiral titanocene catalysts developed by Buchwald et al,5a,b and their Zr analogues,5c were found to be particularly effective in the hydrogenation of cyclic imines. While Ru6, 7 and Rh8 complexes have been successfully employed in imine hydrogenations6, 8ae, g and in asymmetric transfer hydrogenations,7, 8f they have also been found to be effective in the reduction of cyclic and acyclic imines, sulfonimines,6a, 7c and the direct reductive amination of ketones 8c,g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years a variety of chiral metal catalysts have been successfully applied to this reaction. The chiral titanocene catalysts developed by Buchwald et al,5a,b and their Zr analogues,5c were found to be particularly effective in the hydrogenation of cyclic imines. While Ru6, 7 and Rh8 complexes have been successfully employed in imine hydrogenations6, 8ae, g and in asymmetric transfer hydrogenations,7, 8f they have also been found to be effective in the reduction of cyclic and acyclic imines, sulfonimines,6a, 7c and the direct reductive amination of ketones 8c,g.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these procedures often require high catalyst loadings, elevated pressures, and long reaction times to obtain the desired amines in high yields and with high ee 's. Although several useful methods have been described for the hydrogenation of cyclic imines,5c, 7b, 9h, 14 the enantioselective hydrogenation of acyclic imines is more difficult to achieve 1. The process is also sometimes further complicated by the interconversion between E and Z isomers of an acyclic imine in solution 5a,b…”
Section: Introductionmentioning
confidence: 99%
“…We are not the first to assert this claim; several research groups were cognizant of or invoked ligand distortions as being responsible for stereoinduction in Jacobsen-Katsuki-type catalysts, 11,[13][14][15][16][17] bisoxazolinyl-type catalysts, [18][19][20] porphyrins, 21,22 biaryls, [23][24][25] and there are examples in the literature where flexible ligands can be locked into an asymmetric shape so that good ee's are noted. [26][27][28][29][30] The difference between these studies and ours is that we can quantify how much chirality is associated with each of these distortions. In this article we report on several distortion modes available to this ligand and demonstrate that one or more such modes can significantly increase the chirality content of this catalyst.…”
mentioning
confidence: 80%
“…We are not the first to assert this claim; several research groups were cognizant of or invoked ligand distortions as being responsible for stereoinduction in Jacobsen-Katsuki-type catalysts, 48 [62][63][64][65][66] The difference between those studies and the computational assessment described here is that we can quantify how much chirality is associated with each of these distortions.…”
Section: Figure 21mentioning
confidence: 93%